2011
DOI: 10.1002/app.34079
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced effects in gamma‐irradiated PLLA and PCL at ambient and dry ice temperatures

Abstract: The effect of c-rays sterilization at ambient (23 C) and at dry ice temperatures (À78 C) on two biodegradable semicrystalline polyesters, namely poly(L-lactide) (PLLA) and poly(e-caprolactone) (PCL), was studied. The radical processes generated by irradiation were investigated by electron paramagnetic resonance (EPR) spectroscopy, whereas postradiation changes were monitored for 5 months by scanning calorimetry, thermogravimetric analysis, and apparent viscosity measurements. It was confirmed that the radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…However, the same irradiation cross‐links the chains increasing weight average molecular weight ( M w ). Increase of M w might result in increase of stiffness and strength of the polymer …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same irradiation cross‐links the chains increasing weight average molecular weight ( M w ). Increase of M w might result in increase of stiffness and strength of the polymer …”
Section: Discussionmentioning
confidence: 99%
“…Increase of M w might result in increase of stiffness and strength of the polymer. 48,49 Scaffold with high open interconnected porous network stimulates and supports bone ingrowth as well as subsequent remodeling and maturation by providing optimal stiffness and external and internal geometrical shapes. 37,40 The cell study showed that pore shape and size play a significant role for seeding efficiency and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations are likely due to a combination of factors: Swelling of the substrate by the monomer solution; the production of α-carbon radicals that are stabilized by the carbonyl groups in both PCL and PAA 40,41 while the β-radicals formed in methacrylates are less stable; 40 and the high G-value for decarboxylation of PAA. 42 With only limited solubility parameters available for the substrates investigated, the first point cannot be properly evaluated.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The effect of ionizing radiation on PLLA has been reported by several authors, either by gamma or electron beam [26][27][28]. Commonly, irradiation agents, such as triallyl isocyanurate, were used to improve strength by crosslinking the polymer chain.…”
Section: Introductionmentioning
confidence: 99%